2015
DOI: 10.1101/cshperspect.a017558
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Sexually Antagonistic Phenotypes

Abstract: Sexual conflict occurs whenever there is sexually antagonistic selection on shared traits. When shared traits result from interactions (e.g., mating rate) and have a different genetic basis in each sex (i.e., interlocus conflict), then sex-specific traits that shift the value of these interaction traits toward the sex-specific optimum will be favored. Male traits can be favored that increase the fitness of their male bearers, but decrease the fitness of interacting females. Likewise, female traits that reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 130 publications
(179 reference statements)
1
52
0
Order By: Relevance
“…Even in the absence of a shared genetic architecture, both natural selection and neutral evolution might result in a pattern of correlated trait evolutionfor example, if either process generates population variation in one sex and the opposite sex then evolves in concertin contrast to true coevolution. Indeed, the relative contribution of the ecological setting in shaping the evolution of sexually antagonistic traits is a key and open question in the field (Arnqvist & Rowe 2005;Fricke et al 2009;Arbuthnott et al 2014;Perry & Rowe 2014;Anderson & Langerhans 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Even in the absence of a shared genetic architecture, both natural selection and neutral evolution might result in a pattern of correlated trait evolutionfor example, if either process generates population variation in one sex and the opposite sex then evolves in concertin contrast to true coevolution. Indeed, the relative contribution of the ecological setting in shaping the evolution of sexually antagonistic traits is a key and open question in the field (Arnqvist & Rowe 2005;Fricke et al 2009;Arbuthnott et al 2014;Perry & Rowe 2014;Anderson & Langerhans 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Theory predicts that IaSC and IeSC are intricately linked (Arnqvist and Rowe 2005;Bonduriansky and Chenoweth 2009;Perry and Rowe 2014). IaSC could, for example, arise whenever IeSC over optimal mating rates spurs coevolution of interacting male and female reproductive traits that, to some extent, share a common genetic basis in the sexes.…”
Section: Introductionmentioning
confidence: 99%
“…In isolation, the influence of all social behaviors on lifespan is eliminated. In same‐sex groups, individuals are able to engage in social interactions, but are not able to reproduce and females are not subject to sexual conflict/female harm, which in the case of flies is very significant (Wigby and Chapman ; Perry and Rowe ). Not surprisingly, we found that the mixed sexes group had a dramatic effect on female lifespan, which is expected given that reproduction (Fowler and Partridge ; Wigby and Chapman ) and exposure to males (Partridge and Fowler ) are both well‐known to decrease female lifespan in fruit flies.…”
Section: Discussionmentioning
confidence: 99%